EVALUATING THE ROLE OF THE USAID IN COMMUNITY BASED SOLID WASTE MANAGEMENT (CBSWM) PROGRAM - Retnayu Prasetyanti (UIN Sunan Kalijaga, 2015)
The existence of international actor has become hot issue in this globalizationworld. Community Based Solid Waste Management (CBSWM) program is one ofthe commitment of The United States Agency for International Development(USAID) in helping Indonesian government reducing the environmental problems,particularly the problem of waste. Just like another program that is needed to beevaluated and improved, CBSWM also has big attention from public community.The real role of USAID in CBSWM raised a lot of question relates to the successof the program. Many people said agree to the effective role of USAID, and so doesthe program of CBSWM. The core point to understand the role of USAID isconsisted to two urgent questions about the perspective of the program implementationand also the impact that community felt. These two perspectives are the main measurementtool to assess the role of USAID and its key learning of success. While in thisresearch, the quantitative approach the researcher used is Analysis of Variance(ANOVA); it is a technique to test a similarity of mean of the variable in the sametime. After that, the analysis of the role of USAID in CBSWM will be derived intheoritical explanation on the sound governance and community empowerment perspective.From this result, the role of USAID was really good in the process ofimplementation and given good impact to the environmental condition, activity andfacility. The failure on the aspect of community welfare does not make a complexproblem since the main purpose of the program is in the context of environment. Thesuccess of CBSWM program not only comes from the serious role of USAID, itneeds community and government total support. Local government and communityneed to hold a closer partnership to maximize the result USAID has achieved and to make a better condition of community welfare. A good quality life of community willdetermine a good condition of environment.Keywords: Globalization, International Actor, USAID, Sound Governance,Community Empowerment